Comparative Online Marketing Strategies (Social Media) With Offline (Personal Selling) At Tridaya Creative Agency Event Organizer : Comparative Study Of Marketing Strategies at Tridaya Creative Agency - Muhamad Omar Qilya Alrizis; Nurul Asfiah; Immanuel Mu’ammal (Tourism Department, State Polytechnic of Banyuwangi, 2024)
This study aims to determine the application of social media marketing strategies and personal selling and compare the two strategies at the event organizer tridaya creative agency. This research was conducted at Tridaya creative agency, the type of research used is comparative with a qualitative approach. Data collection was carried out in three ways, namely, the first by using the interview method of the tridaya creative agency, observation or direct observation when research was conducted and the last method with documentation. The data analysis method is carried out in three stages, namely data reduction, data appearance and conclusion drawing. The results of this study indicate that the personal selling marketing strategy is more optimal and effective in its implementation. This is because the personal selling strategy applies a comprehensive strategy process compared to the social media strategy.